The Effectiveness of an Environment-Based Biodiversity Flipbook E-Module on Students’ Biology Understanding and Scientific Process Skills in Grade X of SMA Negeri 21 Medan - Lusiana Rumapea; Masdiana Sinambela; Melva Silitonga (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to analyze the effectiveness of an environment-based Biodiversity Flipbook E-Module in improving tenth-grade students’ understanding of biology and their scientific process skills at SMA Negeri 21 Medan. The study employed a one-group pretest–posttest design involving 36 students. Research instruments included a validated biology comprehension test and an observation sheet used to assess students’ scientific process skills during three environment-based learning sessions. Data were analyzed using the N-gain score and descriptive statistics. The results showed that the mean pretest score of 33.81 increased to 83.88 in the posttest, resulting in an N-gain score of 0.76, which falls into the high category. Students’ scientific process skills were classified as very good across all learning sessions and demonstrated an increasing trend during the final meeting. These findings indicate that the environment-based Biodiversity Flipbook E-Module is effective in enhancing students’ understanding of biological concepts and their scientific process skills through contextual learning grounded in real environmental exploration.